The Larger Moths (Lepidoptera: Heterocera) Of The Crocker Rangenational Park, Sabah: A Preliminary Checklist - Fatimah, Abang; Catherine, Karim (ARBEC Publishing, 2002)
The larger moth fauna of a hill mixed dipterocarp forest at the Crocker Range Park (CRP) was studied from light trap samples. A total of 859 individuals were collected comprising of 370 species from 15 families. A preliminary checklist of the larger moth species collected from the Park is presented. The CRP moth species diversity is found to be considerably high with an observed á of 249.75 ± 28.09. This falls in the 200-400 range as the typical values for the larger moths of Borneo. Of the 15 families encountered, the Noctuidae and Geometridae represent the most diverse families while the three least diverse families are Brahmaeidae, Saturniidae and Bombycidae. None of the Nolidae, Callidulidae, Ratardidae and Zygaenidae were collected. As high as 62% of the total species collected are singletons, comprising of 27% of the total individuals collected. The reason for this is unclear, however, this could indicate that the larger moth fauna of the CRP is highly diverse. Some of these singleton species are recorded as rare in Borneo while the others are either uncommonly encountered or only reported from Borneo. The geometrid Amblychia infoveata Prout and Godonela nora Walker and the eupteroptid Eupterote multiarcuata Holloway were among the most frequently encountered species.